2007
DOI: 10.1111/j.1442-2018.2007.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing competency and organizational climate as perceived by staff nurses in a Chinese university hospital

Abstract: Nursing competency is important to ensure patient safety and improve the quality of nursing care. Based on competency-based human resource management strategies, the organizational climate can positively influence nursing competency. However, a review of the literature indicated that there were no studies about the relationship between nursing competency and organizational climate in the People's Republic of China. This descriptive, correlational study examined the relationship between nursing competency and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
2
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 19 publications
3
22
2
5
Order By: Relevance
“…In Mertojaet al, 17 Ying et al, 18 and Bahraini et al, 14 studies, most of the nurses reported their competence as good, which is not consistent with the results of the present study.…”
Section: Discussioncontrasting
confidence: 86%
“…In Mertojaet al, 17 Ying et al, 18 and Bahraini et al, 14 studies, most of the nurses reported their competence as good, which is not consistent with the results of the present study.…”
Section: Discussioncontrasting
confidence: 86%
“…This is in the same vein of Abd El-Megeed and Ahmed [27] who concluded that the good spirits and relationships, and human treatment between nurses are indicators of open and positive climate. Also, previous researchers found that organizational support, cooperative work environments and fair rewarding were indicators of organizational climate perception [28,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Financial-analysis education for nurses has been reported to lead to effective reallocations of nursing resources, and thus, to reduced costs and increase profits (Finkler et al, 2007;Ying et al, 2007). According to the leadership competency model of the Moses Cone Health System, financial competency is the most important competency expected of future nurse leaders.…”
Section: Discussionmentioning
confidence: 97%